2014
DOI: 10.2337/dc14-0898
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Calcium Levels and Risk of Type 2 Diabetes in Individuals at High Cardiovascular Risk

Abstract: OBJECTIVEInsulin resistance and secretion depend on calcium homeostasis. Cross-sectional studies have associated elevated serum calcium levels with markers of impaired glucose metabolism. However, only one prospective cohort study has demonstrated an increased risk of diabetes in individuals with increased serum calcium concentrations. The aim of the current study was to prospectively investigate the association between albumin-adjusted serum calcium concentrations and type 2 diabetes in subjects at high cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 39 publications
5
85
1
Order By: Relevance
“…However, this study has also shown no relationship between two single nucleotide polymorphisms associated with calcium concentration (rs1801725 and rs17251221) and risk of diabetes. More recently, two other smaller studies have investigated the link between fasting albumin-corrected serum calcium and incident T2DM, reporting positive associations (17,18). Of note, in both studies the Authors acknowledged as a major limitation the unavailability of direct measurement of iCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study has also shown no relationship between two single nucleotide polymorphisms associated with calcium concentration (rs1801725 and rs17251221) and risk of diabetes. More recently, two other smaller studies have investigated the link between fasting albumin-corrected serum calcium and incident T2DM, reporting positive associations (17,18). Of note, in both studies the Authors acknowledged as a major limitation the unavailability of direct measurement of iCa.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, crosssectional and case-control studies investigating the relationship between calcium homeostasis and glucose metabolism have reported conflicting results (7)(8)(9)(10)(11)(12)(13)(14)(15); however, only a few studies have prospectively evaluated the association between serum calcium and risk of incident T2DM, suggesting that higher levels of serum calcium predict an increased risk of T2DM (16)(17)(18). These studies have relied either on total serum calcium or the indirect, albumincorrected estimate of serum calcium: these measurements, however, only approximate the levels biological-active serum calcium (iCa) (19).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in serum calcium concentrations have been associated with an increased risk of type 2 diabetes in individuals at high cardiovascular risk. 24 Insulin secretion is a calciumdependent biological process as it is required for both the first and second phase of insulin secretion, increasing cytosolic calcium has been associated with an increase in the expression of GLUT4 transporters in the myocyte, which, in turn, increases the insulin-stimulated glucose transport activity in these cells. 25 Since hyperinsulinaemia is the predominant finding in type 2 diabetes, this therefore explains the increased calcium levels seen in the diabetic state.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Moreover, several recent studies show that serum calcium levels predict the incidence of type 2 diabetes. [7,8] Experimental data demonstrate that increased cytosolic calcium levels attenuate the effect of insulin on glucose uptake by decreasing insulin receptor activity and reducing glucose transporter expression in adipocytes and muscle cells. [31,32] Lastly, calcium may mediate hemostatic imbalance through increased oxidative stress, which has been implicated as a common pathway promoting atherosclerosis and thrombosis.…”
Section: Cho Et Al Medicine (2016) 95:24mentioning
confidence: 99%
“…Regarding calcium imbalances, considerable evidence shows that hypercalcemia is associated with increased risks of developing of cardiovascular disease (CVD) and mortality. [2] Recent population-based studies indicate that a slight imbalance in serum calcium, even within a normal range, is closely associated with metabolic disorders [3][4][5][6] and predicts development of type 2 diabetes, [7,8] suggesting a physiological link between serum calcium and increased cardiovascular (CV) risk. Although some studies report that high normal serum calcium levels can predict the incidence of myocardial infarction [9] and CV mortality, [10,11] it is still unclear whether slight changes in serum calcium induce CVD.…”
Section: Introductionmentioning
confidence: 99%